The ripple effect of compassion on psychosocial flourishing: A mediational model of individual and organizational factors in Indian public sector - Sheelam Jain; Rajlaxmi Garg (Acta Psychologica)
The study draws insights from the ethos of Buddhism and underpinnings of positive activity model to investigate the mediational role of individual emotions and organizational support in the relationship between workplace compassion and psychosocial flourishing. Data were collected from the employees of a public sector organization in India who were selected using purposive sampling technique. An exploratory sequential mixed method approach was followed, that includes qualitative phase of focus group studies involving 42 participants to identify the main themes of the study, and a theoretical model is proposed following thematic literature review. Quantitative survey responses from 218 employees were used to conduct further statistical analysis. The authors tested the proposed model and hypothesis through parallel mediation analysis using structural equation modelling. Results showed that workplace compassion significantly influences psychosocial flourishing of the compassion givers, positive and negative emotions as well as perceived organizational support significantly and positively mediate compassion and flourishing relationship. Advocating the idea of productive paradox wherein compassion for others leads to utmost self-benefit, the study highlights the reciprocal gains of well-being and fulfillment to compassion giving employees at service-centered workplaces.